1995
DOI: 10.1111/j.2044-8260.1995.tb01456.x
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive estimation in neurological disorders

Abstract: The Cognitive Estimation Test (CET) was devised by Shallice & Evans (1978) in an attempt to quantify the tendency observed in some patients with frontal lobe lesions to produce bizarre estimates in response to questions to which people do not usually know exact answers (e.g. 'what is the height of a double-decker bus?'), despite performing normally on standard intelligence tests. In the present study, the CET performance of a large number of patients suffering from head injury, brain tumour, ruptured aneurysm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(26 citation statements)
references
References 8 publications
1
24
1
Order By: Relevance
“…Thus, cognitive estimation discussed as an executive function was also disturbed in the patients confirming the findings of Kopelman (1991a), Kopelman et al (1999), and Taylor and O'Carroll, (1995). The Korsakoff patients in our study exhibited deficits in all tested estimation dimensions ('size,' 'weight,' 'quantity,' and 'time') whereby time estimations were the most deteriorated.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Thus, cognitive estimation discussed as an executive function was also disturbed in the patients confirming the findings of Kopelman (1991a), Kopelman et al (1999), and Taylor and O'Carroll, (1995). The Korsakoff patients in our study exhibited deficits in all tested estimation dimensions ('size,' 'weight,' 'quantity,' and 'time') whereby time estimations were the most deteriorated.…”
Section: Discussionsupporting
confidence: 75%
“…Though Leng and Parkin (1988) did not find impairments in the Cognitive Estimation Test (CET) of Shallice and Evans (1978) in Korsakoff patients, Shoqueirat, Mayes, MacDonald, Meudell, and Pickering (1990) revised this finding. Comparing the CET performance of patients with different neurological disorders including Alzheimer's disease, head injury, encephalitis and others (Taylor & O'Carroll, 1995) the most pronounced deficits were found in the Korsakoff patients. Kopelman (1991a) on the other hand, observed no differences in the CET performance between patients with Alzheimer's disease and Korsakoff patients whereas in all other tests of frontal functions, Alzheimer patients were more deteriorated.…”
Section: Introductionmentioning
confidence: 99%
“…The CET advantage found in our Italian male participants has previously been reported in other CET studies [5,8,31], including the British sample administered the same CET [7]. While previous CET studies have shown that higher levels of education are associated with lower CET error scores [5,7,8], performance on this Italian version was not related to education.…”
Section: Discussionmentioning
confidence: 34%
“…While previous CET studies have shown that higher levels of education are associated with lower CET error scores [5,7,8], performance on this Italian version was not related to education. This is surprising given that our participants had a wide range of educational levels (ranging from 5 years to 18 years and more) compared to previous studies that have tended to recruit individuals that do not have as low a level of education [7], have only high or low education levels [2,27] or the participants' education levels are not specified [28] and do report education effects.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation